A hora e a vez de Adriana Lunardi: escritas de mulheres e biografema - Jorge, Maria Zeneide de Macedo Melo (2020)
The purpose of this work, “Adriana Lunardi's time and turn: feminine writing and biographeme” is to analyze some narratives contained in Adriana Lunardi's Vésperas, published in 2002, and to make evident the relation of the fictional work with the concept of biographeme, formulated by Roland Barthes, and the intertextuality, that the author uses to build her stories. Biographies are residual traces of a person's life, interpreted by the reader or the biographer. We seek to analyze the composition of the narratives and the effects of this form of organization, revealing the way Adriana Lunardi fictionalizes women writers from these biographies and the contexts that relate to them or give an account of the lives of fictionalized authors. Then, we present the construction of the writer characters that had real existence, which the writer fictionalizes, creating for herself a literary canon of her own, which reflects her condition as a writer in Brazil. At this juncture, it was possible to understand the stories of the characters, and through the considerations observed in the narratives we chose to analyze and discuss the proposal with the intention of verifying the effect of the meanings present in the narrative process erected from fragments of lives, that is, of biographemes.